A contextualização de conhecimentos no ensino de microbiologia com base na teoria da aprendizagem significativa - BEZERRA, Hanna Patrícia da Silva (2016)
This research accomplished an investigation the impacts about the context practice’s activities in the learning process with high school students of the technical course in food in the integrated form, at Campus Macapá of IFAP, from generating theme bacterium in microbiology matter. Two practice activities were developed: yogurt production and analysis of hand hygiene efficiency. The “Bacterium” theme was chosen due to relate to the reality of the students and make the program content of the microbiology matter, considered abstract because of the lectures do not provide a concrete approach of the subjects studied, contributing to only rote learning. For data collect, was used the concept maps technique to compose the empirical material. The students developed the conceptual maps from their previous knowledge, before context practice’s activities and after experiments. The maps were evaluated by the students themselves, through a semi-structured self-assessment by an educator and researcher. The categories of analysis maps were concepts (quantity and quality and conceptual hierarchy levels); interrelationships between concepts (lines inbreeding, number of link words and propositions with logical meaning) and map structure (crossrelations representative of the content and creativity). The results of evaluations of conceptual maps made it possible to verify that the students had previous knowledge about the subject, however, they had difficulty in relating the concepts hierarchically and to form logical propositions, as well as in establishing cross-links between concepts in different contexts. After the completion of contextualization practices, significant improvement was observed in the development of conceptual relationships by students.